Study of Work Engagement, Job Burnout, Organizational Commitment and Turnover itentions of Faculty of Higher Education Institutions - Riaz Ahmed Mangi (JISR Management and Social Sciences & Economics, 2014)
Work engagement and job burnout are emerging areas in research on human resources management and occupational psychology in Pakistan. Lately, research studies on human sources have explored and presented new trends, constructs and aspects. Emerging trends of human resources and particularly employee psychology based on the studies on workers well being at work from the problem-oriented and pathological perspective are initiated. Earlier, the response of employees in stressful condition were analyzed; afterwards the positive psychology at work was introduced e.g., the introduction of work engagement described in firms of vigor, dedication and absorption during performing any job and job burnout, depicted emotional exhaustion, cynicism and lack of professional efficacy.This study focuses on the faculty of higher education institutions and more specifically faculty of higher education institutions in Sindh to investigate and estimate the work engagement, its relationship with organizational commitment and turnover intention and the relation of burnout with work magagement, organizational commitment and turnover intentions of the faculty of the higher education institutions in Sindh. Despite growing literature on work engagement organizational commitment and job burnout and turnover intention in many countries and in cross-occupational organizations, the knowledge and scholastic literature on the conceptualization and evaluation of both occupational and psychological attitudes in Pakistan is yet to be systematically explored. The study seeks to present an understanding on work engagement and organizational commitment, and comprehend the symptoms of burnout and turnover intentions among faculty of selected higher education institutions.A rigorous and detailed discourse over the philosophy of research helped to choose positivist paradigm as the appropriate research methodology for this study. The population for this study comprised faculty members of higher education institutions employing more than 100 faculty members. All the male and female faculty members working in different departments are included in the sample of the study. Convenient sampling method is applied to collect the data. The questionnaire comprised of four parts, including first part related to the demographic profile, second part contains 17 item UWES (Utrecht Work Engagement Scale), third part contains the questions regarding 16 item MBI-GS (Maslach Burnout Inventory- General Survey), and fourth part includes the questions regarding the six items organizational commitment and three item turnover intention amongst faculty of higher education institutions. The statistical tests i.e., correlation and regression are applied to test the hypotheses of the study. The results of the study indicate that there is high level of work engagement and organizational commitment among the faculty of the higher education institutions in Sindh. The job burnout and turnover intentions among the faculty are significantly low. The results how that the level of burnout and turnover intentions among faculty of medical university  high as compared to rural and urban universities. The relationship between the dimensions and the study constructs are significant. All of the study variables are significantly predicting each other either positively or negatively. The work engagement and organizational comminr Acknowledgement are partially mediating between the job burnout and turnover intention of the faculty. The results of the study supported majority of the hypotheses of the study. The findings of study offer some significant implications for the management of the higher education institutions in particular and services organizations in general. The management of the organizations have to define clear line of communication for maintaining level of engagement among the faculty. Reduction of energy is critical for the employees which might create exhaustion and lead to intentions to switch job. Similarly, managers should carefully evaluate employees' needs and make sincere efforts to fulfill those needs for creating commitment among them. The results of the study show that burnout among the junior faculty (male and female) is higher as compared to senior faculty so the management has to understand their psyche for better decisions. The study has some limitations in terms of conceptual framework, methodology and research design. The study also has contextual limitation as it was confined to the higher education institutions in Sindh.